Expansion, Fracturing, and Depoliticisation: UK government anti-trafficking funding from 2011 to 2023 - Sharapov, Kiril; Mendel, Jonathan; Schwartz, Kyle (Anti-Trafficking Review, 2024)
Anti-trafficking policy discourses and funding trajectories in the UK are developing and expanding in a fractured way. This paper demonstrates that current policies and funding allocations primarily focus on supporting specific ‘victims’ and targeting indistinct ‘criminals’, rather than addressing the broader structural issues underlying human trafficking. This focus perpetuates ignorance of harm done at other scales. Supporting migrants who meet a narrow definition of ‘victims’ effaces how government-funded projects and agencies abuse migrants and exacerbate their vulnerability to exploitation. Anti-trafficking funding from the UK’s Official Development Assistance addresses both the individual and structural scales. However, structural problems are often framed as external, neglecting the impacts of UK policies that increase the vulnerability of migrants and low-paid or casualised workers. We also demonstrate that the UK government’s anti-trafficking discourse and funding are increasingly fractured along spatial lines, with a limited emphasis on the rights of exploited individuals outside the UK coinciding with attacks on the rights of migrants inside. Instead of narrow, depoliticised anti-trafficking discourses, it is vital to critique government policies that cause structural harm and amplify migrants’ vulnerability to exploitation. This could involve defunding certain government activities that increase vulnerabilities rather than merely expanding individual-level funding.